DNA methylation of PITX2 predicts poor survival in men with prostate cancer. (October 2014) - Vasiljević, Nataša; Ahmad, Amar S; Carter, Paul D; Fisher, Gabrielle; Berney, Daniel M; Foster, Christopher S; Cuzick, Jack; Lorincz, Attila T
Aim: We investigated if methylation of candidate genes can be useful for predicting prostate cancer (PCa) specific death.Patients & methods: Methylation of PITX2, WNT5a, SPARC, EPB41L3 and TPM4 was investigated in a 1:2 case–control cohort comprising 45 men with cancer of Gleason score ≤7 who died (cases), and 90 men who were alive or died of other causes with survival time longer than the cases (controls). A univariate conditional logistic regression model was fitted by maximizing the likelihood of DNA methylation of each gene versus the primary end point.Results: A 10% increase in methylation of PITX2 was associated with PCa related death with OR 1.56 (95% CI: 1.17–2.08; p = 0.005).Conclusion: Our study strengthens prior findings that PITX2 methylation is useful as a biomarker of poor outcome of PCa and in addition we also suggest that it may be particularly useful in men with low Gleason score.